Unmet needs of patients with chronic obstructive pulmonary disease (COPD): a qualitative study on patients and doctors - Wong, Stalia Siew Lee; Abdullah, Nurdiana; Abdullah, Adina; Liew, Su May; Ching, Siew Mooi; Khoo, Ee Ming; Jiwa, Moyez; Chia, Yook Chin (BioMed Central, 2014)
Background Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease with repeated exacerbations resulting in gradual debilitation. The quality of life has been shown to be poor in patients with COPD despite efforts to improve self-management. However, the evidence on the benefit of self-management in COPD is conflicting. Whether this could be due to other unmet needs of patients have not been investigated. Therefore, we aimed to explore unmet needs of patients from both patients and doctors managing COPD. Methods We conducted a qualitative study with doctors and patients in Malaysia. We used convenience sampling to recruit patients until data saturation. Eighteen patients and eighteen doctors consented and were interviewed using a semi-structured interview guide. The interviews were audio-recorded, transcribed verbatim and checked by the interviewers. Data were analysed using a thematic approach. Results The themes were similar for both the patients and doctors. Three main themes emerged: knowledge and awareness of COPD, psychosocial and physical impact of COPD and the utility of self-management. Knowledge about COPD was generally poor. Patients were not familiar with the term chronic obstructive pulmonary disease or COPD. The word ‘asthma’ was used synonymously with COPD by both patients and doctors. Most patients experienced difficulties in their psychosocial and physical functions such as breathlessness, fear and helplessness. Most patients were not confident in self-managing their illness and prefer a more passive role with doctors directing their care. Conclusions In conclusion, our study showed that knowledge of COPD is generally poor. There was mislabelling of COPD as asthma by both patients and physicians. This could have resulted in the lack of understanding of treatment options, outcomes, and prognosis of COPD. The misconception that cough due to COPD was contagious, and breathlessness that resulted from COPD, had important physical and psychosocial impact, and could lead to social isolation. Most patients and physicians did not favour self-management approaches, suggesting innovations based on self-management may be of limited benefit.